Human‐like adrenal development in wild chimpanzees: A longitudinal study of urinary dehydroepiandrosterone‐sulfate and cortisol. Issue 11 (10th November 2019) - Sabbi, Kris H.; Muller, Martin N.; Machanda, Zarin P.; Otali, Emily; Fox, Stephanie A.; Wrangham, Richard W.; Emery Thompson, Melissa
Abstract: The development of the adrenal cortex varies considerably across primates, being most conspicuous in humans, where a functional zona reticularis–the site of dehydroepiandrosterone‐sulfate (DHEA/S) production–does not develop until middle childhood (5–8 years). Prior reports suggest that a human‐like adrenarche, associated with a sharp prepubertal increase in DHEA/S, may only occur in the genus Pan . However, the timing and variability in adrenarche in chimpanzees remain poorly described, owing to the lack of longitudinal data, or data from wild populations. Here, we use urine samples from East African chimpanzees ( Pan troglodytes schweinfurthii) collected over 20 years at Kanyawara in Kibale National Park, Uganda, to trace the developmental trajectories of DHEAS ( n = 1, 385 samples, 53 individuals) and cortisol ( n = 12, 726 samples, 68 individuals). We used generalized additive models (GAM) to investigate the relationship between age, sex, and hormone levels. Adrenarche began earlier in chimpanzees ( 2–3 years) compared with what has been reported in humans (6–8 years) and, unlike humans, male and female chimpanzees did not differ significantly in the timing of adrenarche nor in DHEAS concentrations overall. Similar to what has been reported in humans, cortisol production decreased through early life, reaching a nadir around puberty (8–11 years), and a sex difference emerged with males exhibiting higher urinary cortisol levels compared with females by early adulthood (15–16 years). Our study establishes that wild chimpanzees exhibit a human‐like pattern of cortisol production during development and corroborates prior reports from captive chimpanzees of a human‐like adrenarche, accompanied by significant developmental increases in DHEAS. While the role of these developmental hormone shifts are as yet unclear, they have been implicated in stages of rapid behavioral development once thought unique to humans, especially in regard to explaining the divergence of female and male social behavior before pubertal increases in gonadal hormones. Abstract : Research Highlights: Adrenal hormones may contribute to prepubertally emerging behavioral sex differences. Developmental shifts in wild chimpanzees' urinary dehydroepiandrosterone‐sulfate (DHEAS) parallel humans' and differ from monkeys'. Wild chimpanzees experience adrenarche and increasing DHEAS levels around 2–3 years. Urinary cortisol generally followed a mammalian developmental pattern but exhibited a human‐like sex difference. Cortisol decreased until a mid‐juvenile nadir, then levels increased, especially among males.